Mechanical properties and durability of calcium carbide kiln dust mortar - Naganathan, Sivakumar; Abdul Latif, Masimawati; Razak, Hashim Abdul; Mustapha, Kamal Nasharuddin; Beddu, Salmia; Mahalingam, B.; Elangovan, G. (IAEME Publication, 2019)
This paper reports an investigational study on the effect of calcium carbide kiln dust (CCKD) in cement mortar and its resistance towards hydrochloric acid attack. Mortar with various CCKD replacement levels from 5 to 40 percent by binder weight were tested. The setting time, consistency, density, compressive strength and the durability tests were evaluated to measure the effect of CCKD in mortar. The durability was assessed in terms of loss of density and strength when the specimen were cured in 5% hydrochloric acid (HCL) solution. The results indicate that CCKD replacement levels from 5 to 20 percent performed on par with control mix in terms of compressive strength, the loss in density and strength were around 30% under acid curing. However, 30% and above CCKD replacement percentage showed low density and compressive strength in both conditions. It is concluded that CCKD can be used as an effective replacement for cement up to 20 percent without affecting the performance. © IAEME Publication.